Interactive effects of LPS and dentine matrix proteins on human dental pulp stem cells. (17th February 2018) - Widbiller, M.; Eidt, A.; Wölflick, M.; Lindner, S. R.; Schweikl, H.; Hiller, K.‐A.; Buchalla, W.; Galler, K. M.
Abstract: Aim: To investigate the combinatorial effects of lipopolysaccharide (LPS) and extracted dentine matrix proteins (eDMP) on regenerative and inflammatory responses in human dental pulp stem cells (DPSCs). Methodology: Culture media were supplemented with several concentrations of LPS, eDMP and combinations of both. Cell viability was assessed over 1 week by MTT assay; cell survival was evaluated after 24 h and 7 days by flow cytometry. The expression of mineralization‐associated marker genes was determined by real‐time quantitative polymerase chain reaction (RT‐qPCR). To analyse the inflammatory response, secretion of interleukin 6 (IL‐6) was quantified in the initial and the late phase of cell culture by enzyme‐linked immunosorbent assay (ELISA). Data were treated nonparametrically and Mann–Whitney U ‐tests were performed to compare all experimental groups (α = 0.05). Results: Whereas LPS had no impact on viability, eDMP led to a concentration‐dependent decrease, which was significant after 7 days ( P  ≤ 0.024). A moderate decline of cell survival induced by LPS was detected after 48 h ( P  ≤ 0.026), whereas eDMP was able to reverse this effect. eDMP alone caused increased expression of tested marker genes, LPS had no regulatory effect. Combined eDMP and LPS induced an upregulation of collagen type I and osteocalcin, whereas expression levels of dentine matrix acidic phosphoprotein and dentine sialophosphoprotein were similar to the control. IL‐6‐secretion was increased by LPS over time. eDMP markedly elevated initial production of IL‐6 ( P  ≤ 0.002), but suppressed LPS‐induced cytokine production in the later phase. Conclusions: Lipopolysaccharide did not affect cell viability but interfered with odontoblast‐like cell differentiation of DPSCs. Proteins from the dentine matrix may have a protective effect, attenuate the detrimental impact of LPS and thus play an important role during pulp repair.